2019
DOI: 10.17221/156/2018-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effect on sports performance traits in horses

Abstract: The aim of the study was to estimate the direct additive genetic effect and the additive maternal effect on the level of traits estimated during the Polish Jumping Championships for Young Horses. The investigations involved 541 stallions and 353 mares, which in total started in the Championships 1232 times. Variance and covariance components were estimated using the Gibbs sampling method. Heritability (h<sup>2</sup>) and repeatability (r<sup>2</sup>) coefficients as well as maternal eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Grape pomace bioactive substances seem to be a promising feed ration component because of their positive effect on growth performance, total apparent digestibility and potentially better nutrient utilisation from feed rations without negative effects on animal health (Galik et al 2019). As Somogyvari et al (2018) and Prochniak et al (2019) reported, sport horses should be used as an optimal representative model in digestibility trials with horses. Currently, there is only limited information about feeding grape pomace to horses.…”
mentioning
confidence: 99%
“…Grape pomace bioactive substances seem to be a promising feed ration component because of their positive effect on growth performance, total apparent digestibility and potentially better nutrient utilisation from feed rations without negative effects on animal health (Galik et al 2019). As Somogyvari et al (2018) and Prochniak et al (2019) reported, sport horses should be used as an optimal representative model in digestibility trials with horses. Currently, there is only limited information about feeding grape pomace to horses.…”
mentioning
confidence: 99%
“…Another reason might be related to the maternal effects. Próchniak et al (2019) have reported that the maternal effects influence the performance of horse sports. In this study, the maternal effects on BW and HW at all ages and HG at 0–2 months of age were moderate.…”
Section: Resultsmentioning
confidence: 99%
“…Pr ochniak et al (2019) have reported that the T A B L E 8 Results of factor analysis of birth cannon circumference and the estimated cannon circumference Note: S is sex (effect of colt); BD is birth date; W is weight of mare; IC is inbreeding coefficient; σ 2 uD is the effect of dam; σ 2 uS is the effect of sire; σ 2 uY is the effect of the birth year; σ 2 uA is the effect of dam age; and σ 2 e is the residual effect.…”
mentioning
confidence: 99%
“…However, there are some studies that statistically examined the influence of maternal lineages on sport performance. Polish jumping breeds and their performance during the three-day Polish Championships for Young Horses were studied by the authors of [25]. The maternal impact, defined as the proportion of the total variance explained by the maternal additive genetic variance, was high for all traits (jumping style score, penalty score for each day, and overall rating), ranging from 0.11 to 0.39.…”
Section: Mitochondrial Haplogroups and Performancementioning
confidence: 99%